2018
DOI: 10.3347/kjp.2018.56.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protective Immune Response Induced by a DNA Vaccine Encoding GRA8 against Acute Toxoplasmosis in a Murine Model

Abstract: Toxoplasma gondii is an apicomplexan zoonotic protozoan parasite that infects most species of warm-blooded animals, including humans. The heavy incidence and severe or lethal damage caused by T. gondii infection clearly indicate a need for the development of an effective vaccine. T. gondii GRA8 is a member of the dense granules protein family and is used as a marker of acute infection. In the present study, we evaluated the protective immunity induced by DNA vaccination based on a recombinant eukaryotic plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…After muscle injection, ELISA showed that the antibody level of anti‐TsE in the serum of mice immunized with pcDNA3.1‐TsE was significantly higher than those in the pcDNA3.1 group (Zhang et al, 2020). Moreover, BALB/c mice inoculated with recombinant eukaryotic plasmids expressing Toxoplasma gondii dense granules (GRA8) had higher IgG antibody titers (Chu et al, 2018). Meanwhile, high antibody levels were detected in host induced by pcDNA3.1‐HlLIP in our study, which was in accordance with the humoral immune results of endoparasite DNA vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…After muscle injection, ELISA showed that the antibody level of anti‐TsE in the serum of mice immunized with pcDNA3.1‐TsE was significantly higher than those in the pcDNA3.1 group (Zhang et al, 2020). Moreover, BALB/c mice inoculated with recombinant eukaryotic plasmids expressing Toxoplasma gondii dense granules (GRA8) had higher IgG antibody titers (Chu et al, 2018). Meanwhile, high antibody levels were detected in host induced by pcDNA3.1‐HlLIP in our study, which was in accordance with the humoral immune results of endoparasite DNA vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…T. gondii tachyzoite actively invades nucleated cells of the host, and surface antigens, micronemal proteins, dense granule proteins, and rhoptry protein family proteins all play important roles in this process. Researchers have investigated various types of vaccines based on invasion and virulence-related proteins, such as SAG1, SAG2, and SAG3; MIC1, MIC2, MIC3, MIC5, MIC6, and MIC8; GRA1, GRA2, GRA4, GRA6, GRA7, GRA24, and GRA25; and ROP2, ROP8, ROP17, ROP18, and ROP35 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Compared to other vaccines, DNA vaccines offer many benefits of low cost, safety, and ease of preservation, among other things [ 19 ].…”
Section: Introductionmentioning
confidence: 99%